Pengaruh Pemberian Kombinasi Terapi Batimung dan Aromaterapi Lavender terhadap Peningkatan Kualitas Tidur Ibu Postpartum - Hamsiah Hamsiah; Ryzky Diah Anggraini (Universitas Hang Tuah Pekanbaru, 2026)
Sleep disruptions after postpartum might impair mother recovery owing to hormonal changes, exhaustion, and psychological stress. Batimung and lavender aromatherapy will be tested for their effects on postpartum moms' sleep. This quasi-experimental research separated 30 postpartum moms into intervention and control groups using purposive selection and a pretest–posttest control group technique. The intervention group got batimung treatment and lavender aromatherapy for six days, whereas the control group received simply lavender. Pittsburgh Sleep Quality Index (PSQI) and Wilcoxon Signed Rank and Mann-Whitney tests examined sleep quality. Both groups saw substantial improvements in sleep quality (p < 0.001), with the intervention group having a considerably lower PSQI score (p = 0.003). Batimung and lavender aromatherapy improve postpartum moms' sleep quality more effectively and might be used as a non-pharmacological intervention in obstetric care.